THE GROWTH OF LOCAL TREE SPECIES ON POST-COAL MINING AREAS IN EAST KALIMANTAN - Burhanuddin Adman; Ardiyanto Wahyu Nugroho; Ishak Yassir (Indonesian Journal of Forestry Research, 2020)
Post-coal mining areas need rehabilitation to restore its functionality. Not all plants could grow well on bare ex-coal mining area because of the excessive light intensity and extreme temperature fluctuations.  This study is aimed to determine suitable local tree species for rehabilitating mined areas. Planting was carried out in November 2012, and observations were made in November 2015. The study site was in the district of Samboja, Kutai Kartanegara, East Kalimantan Province, Indonesia. Research results revealed that seven tree species survived well in the ex-coal mining land, i.e., Vitex pinnata L., Syzygium scortechinii (Merr.) Merr. & Perry, Syzygium polyanthum (Wight) Walp., Shorea balangeran (Korth.) Burck, Macaranga motleyana (Mull.Arg.) Mull.Arg., Cleistanthus myrianthus (Hassk.) Kurz and Syzygium lineatum (DC.) Merr. & L.M. Perry. From the seven species V. pinnata, Sy. scortechinii and Sy. polyanthum performed best in both survival and growth rates. This study suggests those three species are excellent local tree species for ex-coal mining rehabilitation, not only because of their high survival rate (≥80%) and fast-growing but also they produce favourable fruits and flowers for wildlife.